Complexation and stability of the fungicide penconazole in the presence of zinc and copper ions. (27th February 2020) - Kovač, Ishak; Jakl, Michal; Fanfrlík, Jindřich; Andrushchenko, Valery; Jaklová Dytrtová, Jana
Abstract : Rationale: For the risk assessment of penconazole in the environment and the evaluation of the possible consequences of its use, it is important to determine how its reactivity and degradation are influenced by metals commonly found in nature, such as copper and zinc. Methods: Changes in the reactivity of penconazole in the presence of zinc/copper ions were studied using electrospray ionisation mass spectrometry and density functional theory calculations. Results: Many penconazole complexes with copper and zinc ions were created; a comparison of the elements showed that a few complexes were formed analogously (doubly charged complexes with four penconazole molecules, singly charged complexes with chlorine as a counterion and singly charged complexes with deprotonated penconazole as a counterion). The metal complexes with different structures indicated different reactivity of penconazole with copper and zinc. Conclusions: The experimental and computational approaches have revealed different changes in the structure of penconazole. In the Zn(II) complex, penconazole deprotonated to stabilise the bond to Zn(II). In the Cu(II) complex, it loses one chlorine atom, creates an additional ring between the triazole ring and the phenyl ring, and/or creates a double bond in the short aliphatic chain.